El 'principio de responsabilidad' de Hans Jonas a la luz de la conciencia ecológica - González Gómez, Germán (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Today we are immersed in a technological era in which human being has the power to dominate nature at will -a power that he prides himself on. This power has got such great dimensions and implications that a new knowledge is strongly required to counter it: possibly, an ethics with predictive power such as Hans Jonas´s imperative of responsibility. The promise of technological progress has become a threat and its environmental consequences have facilitated the emergence of the ecological awareness, giving rise to eco-ethics as its theoretical realization. The link between both ethics is evidenced in the precautionary principle, an attitude of alertness and constraint against the risks of the current technoscientific civilization.
Keywords: Environmental awareness; eco-ethics; Hans Jonas; Imperative of Responsibility; Precautionary Principle